Carbon‐Rich Nonprecious Metal Single Atom Electrocatalysts for CO2 Reduction and Hydrogen Evolution. Issue 10 (9th May 2019) - Wang, Tingting; Zhao, Qidong; Fu, Yuanyuan; Lei, Chaojun; Yang, Bin; Li, Zhongjian; Lei, Lecheng; Wu, Gang; Hou, Yang
Abstract: Single atom catalysts (SACs) are considered as the emerging catalysts for boosting electricity‐driven CO2 reduction reaction (CRR) and hydrogen evolution reaction (HER). To replace the rare and expensive noble metal electrocatalysts, developing nonprecious metal SACs (NPMSACs) with superior electrocatalytic activity and stability is of paramount importance for achieving high efficiency in CRR and HER. Herein, a brief overview of recent achievements in the carbon‐rich NPMSACs for both CRR and HER is provided. The synthesis strategies and corresponding electrocatalytic performances of various carbon‐rich NPMSACs are discussed in the order of various metals (Ni, Co, Fe, Zn, and Sn for CRR, as well as Ni, Co, Fe, Mo, and W for HER), with a special attention paid to understand the structure–activity relationships. Finally, the remaining challenges and future perspectives for enhancing CRR and HER performance of NPMSACs are outlined. Abstract : Single atom catalysts (SACs) have attracted much research attention as promising catalysts in electrocatalytic applications. Recent progress regarding carbon‐rich nonprecious metal SAC (NPMSAC) electrocatalysts in both electricity‐driven CO2 reduction reaction (CRR) and hydrogen evolution reaction (HER) is summarized. Composition/structure–activity relationships are highlighted, and perspectives toward development of new kinds of carbon‐rich NPMSACs with electrochemical energy related applications are discussed.